2019
DOI: 10.1016/j.joms.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Characteristics of the Upper Airway in Patients With Craniofacial Microsomia?

Abstract: IgAdef, B-cell defects were mainly restricted to surface membrane (sm)IgA 1 PCs and MBCs, with 2 clear subgroups showing strongly decreased numbers of smIgA 1 PCs with mild versus severe smIgA 1 MBC defects and higher frequencies of nonrespiratory tract infections, autoimmunity, and affected family members. Patients with IgG subclass deficiency with IgA deficiency and those with CVID showed defects in both smIgA 1 and smIgG 1 MBCs and PCs. Reduced numbers of switched PCs were systematically found in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 103 publications
2
17
1
1
Order By: Relevance
“…26 Additionally, the literature demonstrates that incidences of breathing complications in HFM are related to severity of mandibular malformation. 4,6,26 A distinction is often made between Kaban-Pruzansky grades I-IIa and IIb-III in the literature, with the latter being considered severe. Sixty percent of the patients in our study had Kaban-Pruzansky scores considered less severe, and of our 40% with severe phenotypes, none had grade III classification.…”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, the literature demonstrates that incidences of breathing complications in HFM are related to severity of mandibular malformation. 4,6,26 A distinction is often made between Kaban-Pruzansky grades I-IIa and IIb-III in the literature, with the latter being considered severe. Sixty percent of the patients in our study had Kaban-Pruzansky scores considered less severe, and of our 40% with severe phenotypes, none had grade III classification.…”
Section: Discussionmentioning
confidence: 99%
“…Severe OSA was observed in patients with severe mandibular hypoplasia (50). In 2019, a crosssectional study by Klazen et al showed by studying CT scans of 79 patients with CFM and 88 controls that patients with CFM have a smaller oropharynx volume and retropalatal area compared to controls (51). Patients with CFM and OSA showed, compared to other CFM patients, a smaller retroglossal area and different uniformity and sphericity.…”
Section: Upper Airway Obstructionmentioning
confidence: 99%
“…Patients with CFM and OSA showed, compared to other CFM patients, a smaller retroglossal area and different uniformity and sphericity. Multivariate regression analysis showed sphericity is the main predicting variable for OSA in patients with CFM (51). (50,52)Retrospective data showed that placement of a tracheostomy is often considered a first choice of treatment for patients with CFM and severe OSA (50).…”
Section: Upper Airway Obstructionmentioning
confidence: 99%
“…Airway shape may contribute to the development of OSA [1,10]. Recently, a derived variable, that is sphericity of the upper airway, was suggested and investigated [10,30]. Klazen et al found that less sphericity was the main predictor for OSA in patients with craniofacial macrosomia [30].…”
Section: Plos Onementioning
confidence: 99%
“…Recently, a derived variable, that is sphericity of the upper airway, was suggested and investigated [10,30]. Klazen et al found that less sphericity was the main predictor for OSA in patients with craniofacial macrosomia [30]. It is interesting to note that sphericity had low ICC values for intra-individual repeatability; however, it also showed low variation between T0 and T1 in both the total airway and each segment, all the relative differences being below 15%.…”
Section: Plos Onementioning
confidence: 99%